Factors that Influence Worklife Balance in Distributor Companies in West Jakarta - Islamiati, Diana; Gunawan P, Andreas Wahyu; Aseanty, Deasy (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyse teleworking on work life balance through job motivation, job satisfaction and job performance. The objects in this study were 125 respondents at Distributor Companies in West Jakarta. The method used for sampling in this study is purposive sampling used descriptive statistical data analysis method and using the 22 version of the SEM test. Methods used to conduct field research namely using a questionnaire. This study consisted of one independent variable, namely teleworking, one dependent variable, namely work life balance, and three intervening variables, namely job motivation, job satisfaction, and job performance.